Outlook Alone and in Mixtures for Efficacy in Corn - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2021)
The objective of the study was to compare Outlook (dimethenamid) alone and in various tank mixtures for season-long weed control in corn. Kochia control with most herbicides was 95% or more late in the season. However, Russian thistle control did not exceed 83% with any herbicide tested. Palmer amaranth control at 59 days after the postemergence treatments was similar among all herbicides, while green foxtail control was 93% or more with each treatment. All herbicides increased grain yields relative to the untreated control, but corn treated with Outlook or Verdict alone yielded less grain than the best yielding plots.
Keywords: residual control; tank mixtures; corn